The relationship between smartphone addiction and social anxiety in social media among a group of adolescents using the youth center and affecting factors - Dikeç, Gül; Pirinç, Büşra; Kaya, Beyza; Keleş, Esra; Akın, Esra; Hızmalı, Ahmet; Toprak, Adnan (Journal of Dependence, 2020)
Objective: This study was carried out to determine the relationship between smartphone addiction and social anxiety in social media of adolescents who participating a youth center in Istanbul.Method: This cross-sectional study was conducted between 303 adolescents, 237 women and 66 men, who participated the youth center. In the study, data were collected using the Smartphone Addiction Scale-Short Form (SAS-SF) and Social Anxiety Scale for Social Media Users (SASMU).Results: 78.2% of the participants were women and 21.8% were men, 9.6% were smoke and 5% used alcohol; it was found that using smartphones an average of 4.24 ± 3.08 hours per day. A statistically significant difference was found between the mean scores of the SAS-SF scale according to the sex and internet access of adolescents. Beside, a statistically significant positive moderate correlation was found between the total scores of SAS-SF and SASMU.Conclusion: There seems to be a close relationship between smartphone addiction and social anxiety in social media among adolescents.
Keywords: Smartphone; addiction; community mental health; social anxiety